MEMBANGUN GENERASI SEHAT: PERAN KELUARGA DALAM EDUKASI KESEHATAN REPRODUKSI PADA ANAK - Mediastuti, Fitriani; Khoirunnisa, Endang (Poltekkes Kemenkes Bandung, 2025)
Reproductive health is an essential aspect of child development, yet it is often considered a taboo topic within families. This community service initiative was conducted to strengthen the role of parents in delivering reproductive health education to children at SD Negeri Banteran I, Sleman. The program employed a combination of health education sessions, educational video screenings, interactive discussions, educational games, and knowledge assessments. The target participants were parents of fourth- and fifth-grade students, aiming to enhance their understanding, confidence, and ability to communicate age-appropriate reproductive health information to their children. The results showed a significant improvement in parents’ knowledge, as reflected in the evaluation scores, where participants were able to correctly answer questions they previously misunderstood. Parents also reported feeling more prepared, open, and comfortable discussing reproductive health topics at home. The school responded positively and expressed the importance of continuing similar programs. Overall, this activity demonstrates that a parenting-based educational approach is effective in strengthening family capacity as a key foundation for nurturing a healthy and well-informed younger generation.